Physiotherapy Management in Pneumonia Cases in The ICU: Case Report - Wahyuni, W; Isak, Galih Adi; Prihantoro, Bangkit Dwi; Dwiyanti, Neriza; Fadhilah, Siti; Tomiana, T; Lestari, Dimas Budi; Pabrizadinata, M. Irfan Jasir; Sabana, M. Rajab; Ramadhani, Raden Shafira Saniyyah; Meir, Ruth Golda; Pratiwi, Yunita Rahayu; Salsabila, Brissa Isabel (Academic Physiotherapy Conference Proceeding, 2023)
Introduce: Data from the 2019 Global Burden of Diseases study shows that lower respiratory tract infections including pneumonia and bronchiolitis affect 489 million people worldwide. Children <5 years and adults >70 years are the populations most affected by pneumonia, according to the 2019 GBD study. Purpose: Knowing the physiotherapy management of pneumonia cases in the ICU Methods: using the case report method taken at PKU Yogyakarta Hospital Conclusion: Providing intervention in the form of passive rib torsion in patients in ICU care with the use of ventilators due to pneumonia is considered capable of increasing chest expansion.